Computer architecture : an embedded approach - McLoughlin, Ian. (Singapore : McGraw Hill Education, 2011)
Presents the subject in a readable and interesting format that provides the background and places emphasis on the increasingly important embedded systems that we all rely upon for our day-to-day living. This book addresses the needs of industry, and interlinks with neighbouring electronics, computer engineering within a typical curriculum.
Introduction -- Foundations -- CPU basics -- Processor internals -- Enhancing CPU performance -- Externals -- Practical embedded CPUs -- CPU design -- The future.
Includes index.
Keywords: EMBEDDED COMPUTER SYSTEMS